The Toll-like receptor 4 agonist MRP8/14 protein complex is a sensitive indicator for disease activity and predicts relapses in systemic-onset juvenile idiopathic arthritis. Issue 6 (20th January 2012) - Holzinger, Dirk; Frosch, Michael; Kastrup, Astrid; Prince, Femke H M; Otten, Marieke H; Van Suijlekom-Smit, Lisette W A; Cate, Rebecca ten; Hoppenreijs, Esther P A H; Hansmann, Sandra; Moncrieffe, Halima; Ursu, Simona; Wedderburn, Lucy R; et al.
Abstract : Background: Analysis of myeloid-related protein 8 and 14 complex (MRP8/14) serum concentrations is a potential new tool to support the diagnosis of systemic-onset juvenile idiopathic arthritis (SJIA) in the presence of fever of unknown origin. Objective: To test the ability of MRP8/14 serum concentrations to monitor disease activity in patients with SJIA and stratify patients at risk of relapse. Methods: Serum concentrations of MRP8/14 in 52 patients with SJIA were determined by a sandwich ELISA. The monitoring of therapeutic regimens targeting interleukin 1 and tumour necrosis factor α, and methotrexate treatment was analysed and diagnostic power to predict flares was tested. Results: MRP8/14 levels were clearly raised in active disease and decreased significantly in response to successful treatments. Serum concentrations of MRP8/14 increased significantly (p<0.001) (mean±95% CI 12.030±3.090 ng/ml) during disease flares compared with patients with inactive disease (864±86 ng/ml). During clinical remission MRP8/14 serum levels of >740 ng/ml predicted disease flares accurately (sensitivity 92%, specificity 88%). MRP8/14 levels correlated well with clinical disease activity, as assessed by physician's global assessment of disease activity (r=0.62), Childhood Health Assessment Questionnaire (r=0.56), active joint count (r=0.46) and with C-reactive protein (r=0.71) and erythrocyte sedimentation rate (r=0.72) (for all p<0.001). Conclusion: MRP8/14 serum concentrations correlate closely with response to drug treatment and disease activity and therefore might be an additional measurement for monitoring anti-inflammatory treatment of individual patients with SJIA. MRP8/14 serum concentrations are the first predictive biomarker indicating subclinical disease activity and stratifying patients at risk of relapse during times of clinically inactive disease.